Wireless near-infrared spectroscopy of skeletal muscle oxygenation and hemodynamics during exercise and ischemia. Issue 5 (2009) - Shadgan Shadgan, Babak Babak; Reid Reid, W. Darlene W. Darlene; Gharakhanlou Gharakhanlou, Reza Reza; Stothers Stothers, Lynn Lynn; Macnab Macnab, Andrew John Andrew John
Abstract : The majority of in vivo applications of near-infrared spectroscopic (NIRS) monitoring use continuous wave instruments that require a fiberoptic cable connection between the subject and the instrument during monitoring. In studies of muscle physiology where subjects are exercising, and particularly in those who are engaged in sports activity, a wireless instrument with telemetric capacity provides obvious advantages. Having access to reliable telemetric NIRS technology will also increase the practicality and scope of this biomedical monitoring technique in clinical settings. We report the feasibility of using a wireless continuous wave NIRS instrument with light emitting diodes, spatially resolved configuration, and Bluetooth ® capability to study skeletal muscle oxygenation and hemodynamics during isometric contraction and ischemia induction. In ten healthy subjects comparable patterns of change in chromophore concentration (oxygenated and deoxygenated hemoglobin), total hemoglobin and muscle oxygen saturation were observed during 3 sets of isometric voluntary forearm muscle contraction at 10, 30 and 50% of maximum voluntary capacity (MVC), and a period of ischemia generated subsequently. This small series indicates that data with good intra- and inter-subject reproducibility that is free of movement artifact can be obtained with the wireless NIRS instrument described. The validity of these muscle studies demonstrate a basis for applying wireless NIRS monitoring to other biomedical applications.